Migrant settlement distribution in urban centers of megacities Jakarta - Nandi Nandi (E3S Web of Conferences)
Rapid movement of people and goods has been a remarkable distinction of Jakarta. Apart from being seen as center of development, Jakarta has also been perceived to seek better life and find new opportunities. This cultural phenomenon attracts people from various locations and socioeconomic backgrounds to settle, both permanently or temporarily. The presence of migrants in Jakarta plays an important role toward social and economic aspects. This research discusses; (1) migrant settlement distribution, (2) migrant settlement and its relation to development in urban centers, and (3) socio-economic. To analyze the in-migration phenomenon, this research used Crude In-Migration Rate and on analyzing the distribution of migrant settlements from the urban cores, buffer analysis was implemented. The result of this research shows that migrant settlement in Jakarta does not concentrate on the urban cores or even does not show any possible spread direction toward the core. The dominant migrant settlement and areas with most migrants showed in the southern part of Jakarta Province as it directly connected with South Tangerang City, Depok City, and Bekasi City. Dominant migrant settlement in the west also indicates better transportation and network infrastructure, similar economic activities, and growing livelihood opportunities in southern part of Jakarta.